A systematic review and meta-analysis of psychosocial interventions aiming to reduce risks of suicide and self-harm in psychiatric inpatients. (November 2021) - Yiu, Hin Wall; Rowe, Sarah; Wood, Lisa
Highlights: Psychosocial interventions for self-harm and suicide have an under developed evidence base for acute inpatient settings with only ten randomised controlled trials examining a suicide intervention and none examining self-harm. The most common interventions use to reduce suicide are cognitive behaviour therapy and dialectical behaviour therapy. Psychosocial interventions for suicide do not demonstrate an effect in improving suicidality, depression or hopelessness. Further research is needed to draw firm conclusions about the efficacy of psychosocial interventions for self-harm and suicide in inpatient settings. Abstract: Psychosocial interventions, such as Cognitive Behavioural Therapy (CBT), are often recommended in UK clinical guidelines to reduce suicidality and self-harm in service users with serious mental health problems, but the effectiveness of these interventions in acute mental health inpatient settings is not established. The aim of this study is to examine the types, and effectiveness of psychosocial interventions in inpatient settings in reducing the risk of self-harm and suicidality. A systematic review and meta-analysis was conducted of randomised controlled trials (RCTs) examining the efficacy of suicide and self-harm focused inpatient psychosocial interventions on suicidality (primary outcome), depression, hopelessness and suicide attempts (secondary outcomes). A total of ten studies met eligibility criteria were included in this review. All had low to moderate risk of bias for majority of the indicators, except for blinding of participants where all studies had high risk of bias. All studies examined psychosocial interventions for suicide reduction and none examined a psychosocial intervention for self-harm. The majority of the psychosocial interventions were CBT and Dialectical Behavioural Therapy (DBT). The interventions were no more effective than control treatments in reducing suicidality, depression, hopelessness or suicide attempts post-therapy and at follow-up. However, the majority were small pilot or feasibility RCTs. In conclusion, the finding from this review suggests that psychosocial interventions are not any more effective in reducing suicidality in acute mental health inpatient settings than control interventions. However, a large-scale RCT examining a psychosocial intervention for suicide is needed to provide conclusive findings. There were also no identified RCTs examining self-harm interventions indicating a need to conduct research in this area.